Dynein Heavy Chain 64C Differentially Regulates Cell Survival and Proliferation of Wingless-Producing Cells in Drosophila melanogaster. - Kim, J.Y.; Tsogtbaatar, O.; Cho, K.O. (Journal of developmental biology, 2021)
Dynein is a multi-subunit motor protein that moves toward the minus-end of microtubules, and plays important roles in fly development. We identified Dhc64Cm115, a new mutant allele of the fly Dynein heavy chain 64C (Dhc64C) gene whose heterozygotes survive against lethality induced by overexpression of Sol narae (Sona). Sona is a secreted metalloprotease that positively regulates Wingless (Wg) signaling, and promotes cell survival and proliferation. Knockdown of Dhc64C in fly wings induced extensive cell death accompanied by widespread and disorganized expression of Wg. The disrupted pattern of the Wg protein was due to cell death of the Wg-producing cells at the DV midline and overproliferation of the Wg-producing cells at the hinge in disorganized ways. Coexpression of Dhc64C RNAi and p35 resulted in no cell death and normal pattern of Wg, demonstrating that cell death is responsible for all phenotypes induced by Dhc64C RNAi expression. The effect of Dhc64C on Wg-producing cells was unique among components of Dynein and other microtubule motors. We propose that Dhc64C differentially regulates survival of Wg-producing cells, which is essential for maintaining normal expression pattern of Wg for wing development.